Analisis Anatomi Dan Fisiologi Sistem Indera Pendengaran - Chyntia Riya Ananda; Nining Nidhiawati; Novia Ayu Puspita; Puja Risma Eka Pinasti; Liss Dyah Dewi Ariani (Student Research Journal, 2024)
The sounds heard by the human ear change from mechanical acoustic signals to electrical signals which are transmitted by the auditory nerve to the brain. The process of hearing certainly cannot be separated from the human hearing organ, namely the ear.The ear consists of three basic parts, namely the outer ear, middle ear and inner ear. Each part of the ear works with a specific task to detect and interpret sounds. The main function of the outer ear is to collect and connect sounds to the external acoustic meatus. The middle ear consists of 3 bones (ossicles) which will amplify the pressure 20 times from sound waves to produce fluid vibrations in the cochlea. In the inner ear there is the cochlea, the basilar membrane forms the basis of the cochlear duct. High frequency resonance of the basilar membrane occurs near the base, where sound waves enter the cochlea through the oval window and low frequency resonance occurs near the apex. Inner hair cells that convert the mechanical force of sound (vibrations of cochlear fluid) into auditory electrical impulses (action potentials that convey auditory messages to the cerebral cortex)